IMPLEMENTASI NILAI PANCASILA DALAM PENEGAKAN HUKUM MARITIM DI INDONESIA - Emha, Faresh; Arsanti, Meilan (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2025)
Pancasila as a value system has been rooted in the life of the Indonesian nation, but Pancasila is only used as an identity. However, it has never been manifested in the life of the nation and state, especially in the process of law enforcement. The research method used is normative juridical. The purpose of this study is to examine the Paradigm of Law Enforcement in Indonesia, analyze the implementation of Pancasila values ​​in current law enforcement, and to analyze the concept of Pancasila towards the practice of law enforcement in Indonesia. The weakness of law enforcement in Indonesia is caused by law enforcement officers who fail to interpret national law based on Pancasila values, such as honesty, transparency, and justice. The paradigm of law enforcement that is oriented towards the economy and power must be replaced with an approach that emphasizes morality, humanity, and social welfare in accordance with the principles of Pancasila. Reform is needed, especially in the mentality and integrity of law enforcement officers, as well as the eradication of the legal mafia that damages institutions such as the prosecutor's office and the police. Pancasila must be implemented in character formation and legal decisions to create social justice, legal justice, and legal protection for all Indonesian people, making it the basis for national development and better law enforcement.